Knowledge, attitude, motivation and planning of breastfeeding: a cross-sectional study among Jordanian women - Wasim Khasawneh; Khalid Kheirallah; Mai Mazin; Sanaa Abdulnabi (BMC, 2020)
Abstract Background In Jordan, the rate of exclusive breastfeeding is declining. The trend variation in breastfeeding practice is determined by different factors including antenatal women's attitude and planning which are affected by their awareness and the support they receive. This study aims to assess knowledge, attitude, support, and planning of breastfeeding among Jordanian women. Methods A face-to-face cross-sectional semi-structured questionnaire survey was conducted among healthy women in the antenatal clinic and postpartum ward at three hospitals in Northern Jordan during the period August 2019 to December 2019. Data were collected about demographic characteristics, women's knowledge and attitude towards breastfeeding, antenatal and postnatal support and counseling, and feeding planning. Customized scales were utilized to assess knowledge and attitude. Factors associated with planning to breastfeed were reported. Results 660 women completed the survey questionnaire. The majority were 20 to 35 years of age, 10% were primiparous, and 30% were employed. 78% were knowledgeable about breastfeeding benefits and aware of WHO recommendations. 72% had a positive attitude towards breastfeeding. More than half received support from their husbands to breastfeed their infants, while less than 20% received any counseling from their obstetric providers. 97% reported their intention to breastfeed, and more than half indicated their willingness to breastfeed exclusively. With multivariable logistic regression modelling, predictors of EBF planning include: primiparity (AOR 1.79; 95% CI 1.1, 3.25), positive attitude (AOR 1.80; 95% CI 1.05, 3.1) and positive husband's support (AOR 1.92; 95% CI 1.18, 3.15). Barriers include women's employment (AOR 0.43; 95% CI 0.26, 0.70) and low birthweight (AOR 0.46; 95% CI 0.25, 0.84). Conclusion Jordanian women are highly knowledgeable about breastfeeding benefits, and they exhibit a positive attitude towards breastfeeding resulting in a very high percentage intending to breastfeed their infants. Limited counseling about breastfeeding is a major gap in antenatal care. As intentions might not reflect the actual practice after delivery, gaps and barriers affecting the determinants of successful breastfeeding should be identified, and corrective tools should be implemented accordingly. Allocating a specific time for antenatal or postnatal counseling and support is expected to promote breastfeeding practice in our population.